Prognostic value of preoperative serum tumor markers in gastric cancer - Huang, Ze-Bo (Baishideng Publishing Group Co., Limited, 2014)
AIM: To evaluate the prognostic value of preoperative carcinoembryonic antigen (CEA), carbohydrate antigen (CA)19-9, and CA50 in patients undergoing D2 resection. METHODS: We evaluated 363 patients with gastric cancer who underwent gastrectomy at our hospital from January 2006 to December 2009. Blood samples were obtained from each patient within 1 wk before surgery. The cut-off values for serum CEA, CA19-9, and CA50 were 5 ng/mL, 37 U/mL, and 20 U/mL, respectively. The correlation between preoperative tumor marker levels and prognosis was studied by means of univariate and multivariate analyses. RESULTS: The preoperative serum positive rates of CEA, CA19-9 and CA50 were 24.0%, 18.9% and 24.5%, respectively. The positivity rate of serum CEA was significantly correlated with age (P < 0.001), sex (P = 0.022), tumor size (P = 0.007) and depth of invasion (P = 0.018); CA19-9 with tumor size (P = 0.042) and lymph node metastasis (P < 0.001); and CA50 only with lymph node metastasis (P = 0.001). In multivariate analysis, tumor size, T category, N category, vascular or neural invasion, and adjuvant chemotherapy were independent prognostic factors for overall survival. CA19-9 had an independent prognostic significance in patients without adjuvant chemotherapy (P = 0.027). CONCLUSION: Preoperative serum CEA, CA19-9 and CA50 are prognostic in patients with gastric cancer. Only CA19-9 is an independent prognostic factor after surgery without adjuvant chemotherapy.